Characterization of the dominant molecular step orientations on hydroxyapatite (100) surfaces - Kwon, Ki-Young (Langmuir : the ACS journal of surfaces and colloids, 2009)
Hydroxyapatite (HAP) is the major inorganic component of bones and teeth. The characterization of HAP surfaces on the molecular level is important for achieving a fundamental understanding of bone remodeling and dental caries processes. On the microscopic level, hydroxyapatite growth and dissolution reactions mainly occur at steps. Therefore, this study focuses on individual molecular steps on HAP (100) facets under both static conditions and dynamic dissolution conditions using atomic force microscopy (AFM). We found that molecular steps parallel to the elongated axes of HAP crystals and those angled approximately 54 degrees against the elongated axis are not only energetically favorable but also kinetically dominant under dissolution conditions